Theatre curriculum in the US: a great tasting sandwich on stale bread. Issue 1 (2nd January 2016) - Duffy, Peter
ABSTRACT: This essay considers the role that local control, poverty, access and policy play in providing drama/theatre education opportunities to students in the US. It examines how state and federal initiatives shape and determine the curriculum. While there are studies that suggest robust theatre education in the US, these findings are complicated when poverty statistics are superimposed upon them revealing inequitable access to theatre curricula. Additionally, race and class influence one's access to in-school theatre curricula. Beyond simply a skills-based definition, maintaining a broad understanding of theatre determines how teachers can impact curricula through adaptation and student-centred practices.